2022
DOI: 10.1093/mnras/stac3487
|View full text |Cite
|
Sign up to set email alerts
|

PDFchem: A new fast method to determine ISM properties and infer environmental parameters using probability distributions

Abstract: Determining the atomic and molecular content of the interstellar medium (ISM) is of fundamental importance to understand the star-formation process. Although there exist various three-dimensional hydro-chemical codes modelling the ISM, they are computationally expensive and inefficient for studies over a large parameter space. Building on our earlier approach, we present PDFchem, a novel algorithm that models the cold ISM at moderate and large scales using functions connecting the quantities of the local (AV, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 210 publications
0
8
0
Order By: Relevance
“…In addition to that and inspired by hydrodynamical simulations that indicate the existence of a connection between the local (effective) A V and the local total number density, we use a variable density slab, which represents the A V -n H relation discussed in Bisbas et al (2019) and Gaches et al (2022). This slab covers densities from 10 2 to 10 5.5 cm −3 and is found to estimate reasonably well the average local PDR conditions of three-dimensional clouds (Bisbas et al 2023). It is thus interesting to explore whether it can reproduce the observed abundances of species.…”
Section: Pdr Modelingmentioning
confidence: 99%
“…In addition to that and inspired by hydrodynamical simulations that indicate the existence of a connection between the local (effective) A V and the local total number density, we use a variable density slab, which represents the A V -n H relation discussed in Bisbas et al (2019) and Gaches et al (2022). This slab covers densities from 10 2 to 10 5.5 cm −3 and is found to estimate reasonably well the average local PDR conditions of three-dimensional clouds (Bisbas et al 2023). It is thus interesting to explore whether it can reproduce the observed abundances of species.…”
Section: Pdr Modelingmentioning
confidence: 99%
“…The abundance ratio between HCO + and 12 CO (hereafter CO if not specified) is a tracer of the CR ionization rate (e.g., Zhou et al 2022;Bisbas et al 2023). To further test this notion in the SNR W28, we calculate the column density of HCO + and CO and their abundance ratio.…”
Section: Column Densities and Abundance Ratio Between 12 Co And Hco +mentioning
confidence: 99%
“…The J = 1-0 lines of HCO + , HCN, and HNC molecules are typical tracers of dense gas (e.g., Shirley 2015). The abundance ratio between HCO + and other specific molecules, for example, CO (e.g., Zhou et al 2018;Bisbas et al 2023), has been proposed to be a tracer of CR ionization (e.g., Albertsson et al 2018), while the line ratio ( ) ( ) I I HCN HNC serves as a tracer of gas kinetic temperature (e.g., Hacar et al 2020). Therefore, observation of these three lines toward W28 provides information on the physical and chemical effects of W28 on its adjacent MCs.…”
Section: Introductionmentioning
confidence: 99%
“…The traditional approach of estimating the number density of GMCs is based on observations of column density and certain assumptions on the geometry of the clouds, for example, a cylindrical geometry for filamentary structures or spherical geometry for dense cores (André et al 2014). Bisbas et al (2021Bisbas et al ( , 2023 proposed an empirical power law to convert the observed column density to the mean number density of GMCs based on the MHD simulations from Wu et al (2017), which works decently but with noticeable scatter. Another method to constrain the number density of GMCs is utilizing density "probes," such as cyanoacetylene Original content from this work may be used under the terms of the Creative Commons Attribution 4.0 licence.…”
Section: Introductionmentioning
confidence: 99%